Indoor Justice: Private Neighborhoods An The Problem Of Privatized Spaces (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Our main goal was to discuss the existence of spaces of legal impunity in private neighborhoods of Buenos Aires, Argentina. We carried out an ethnography in country clubs and private neighborhoods in the Gran Buenos Aires. We also used secondary sources for the scope of this research. We observe that insecurity is one of the main reasons for living in these territories, but within them there is also criminality, only that power and some political ties allow irresolution of such crimes. There is little exploration regarding this topic and we found a lack of bibliography on this issue.
Keywords: common good; urbanization; globalization; gentrification; middle class